Financial Distress Ditinjau dari Kinerja Keuangan dan Ukuran Perusahaan di Indonesia - Adelina Citradewi; Elvira Fitri Darmawanti (Universitas Multi Data Palembang, 2026)
Financial distress is an early sign of a company’s financial problems before bankruptcy occurs. Predicting financial distress is crucial for identifying financial conditions as early as possible so that measures can be taken to prevent undesirable outcomes. This study aims to investigate whether the magnitude of financial ratios and firm size have an impact on financial distress. The focus of this study is on the mining sector listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. The research sample was selected using purposive sampling. E-Views 12 software was used as a tool for panel data analysis to test the relationship between the dependent and independent variables. The results indicate that profitability, liquidity, and leverage influence financial distress, whereas firm size does not. A limitation of this study is that it covers only the mining sector; future research is encouraged to include other sectors using different models.